1999
DOI: 10.1002/(sici)1096-987x(199906)20:8<786::aid-jcc5>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Improving efficiency of large time-scale molecular dynamics simulations of hydrogen-rich systems

Abstract: A systematic analysis is performed on the effectiveness of removing degrees of freedom from hydrogen atoms and/or increasing hydrogen masses to increase the efficiency of molecular dynamics simulations of hydrogen‐rich systems such as proteins in water. In proteins, high‐frequency bond‐angle vibrations involving hydrogen atoms limit the time step to 3 fs, which is already a factor of 1.5 beyond the commonly used time step of 2 fs. Removing these degrees of freedom from the system by constructing hydrogen atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
374
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 802 publications
(377 citation statements)
references
References 29 publications
3
374
0
Order By: Relevance
“…The mass and principal moments of inertia of water sites are increased to optimize the stability of molecular dynamics integration. 81 In particular, the water mass is set to 50 amu (the real value being 18 amu). The chosen principal moments of inertia correspond to a redistribution of water masses as follows: 15 amu for each hydrogen and 20 amu for the oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…The mass and principal moments of inertia of water sites are increased to optimize the stability of molecular dynamics integration. 81 In particular, the water mass is set to 50 amu (the real value being 18 amu). The chosen principal moments of inertia correspond to a redistribution of water masses as follows: 15 amu for each hydrogen and 20 amu for the oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…An unwanted side-effect of the increase in total mass, however, was the scale down of the whole motion of the system (not only the fast, but also the meaningful dynamics). Subsequent studies led to the exploration of the repartitioning of masses (Feenstra et al 1999), such that a heavier mass was assigned to hydrogen atoms and smaller masses were assigned to heavy atoms, with the result being that the total mass was kept constant. The long-time MD simulation with the hydrogen-mass repartitioning (HMR) method (Hopkins et al 2015) reported that a 4-fs time-step provided a numerically safe result and did not influence thermodynamic properties.…”
Section: Future Perspective Of Enhanced Sampling Methodsmentioning
confidence: 99%
“…Therefore, much related to eq. (2.8), we can compute the first derivative of σ I(α,β) : 11) and also the second derivative:…”
Section: Calculation Of the Lagrange Multipliersmentioning
confidence: 99%
“…For a Verlet-like integrator [9,10], stability requires the time step to be at least about five times smaller than the period of the fastest vibration in the studied system [11]. Here is where constraints come into play.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation